Новый двумерный материал для наноэлектроники - Шварц, К.; Даулетбекова, А.; Сорокин, М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
A new two-dimensional material for nanoelectronics